SUSTAINABILITY ACCOUNTING PRACTICES AND CORPORATE PERFORMANCE - Adi Yosra; Eko Prasetyo (Penelitian dan Pengembangan Ilmu, 2026)
The transition to a green economy requires firms to integrate sustainability accounting into strategic decision-making. This study employs a narrative review approach to synthesize literature on the relationship between sustainability accounting and firm performance through the lens of Institutional Theory and Stakeholder Theory. The synthesis indicates that in developed markets, ESG reporting serves as a value-creation mechanism driven by rigorous regulations and sophisticated investors. Conversely, in emerging markets, ESG reporting is often symbolic and susceptible to greenwashing due to weak legal enforcement. Corporate governance is identified as a crucial mediating factor that determines disclosure credibility. This study concludes that enhancing the quality of sustainability information in emerging markets requires strengthening institutional capacity, integrating digital technology, and establishing transparent audit mechanisms.